الأسس الفقهية والثوابت الشرعية في فتاوى الإمام القرضاوي المتعلقة بالقضية الفلسطينية = The jurisprudential foundations and Shari`ah constants in Imam al-Qaradawi’s fatāwā related to the Palestinian issue - Salhab, Belal Barakat Sulaiman; Zaroum, Abdulhamid Mohamed Ali; Awad, Hany (International Islamic University Malaysia, 2025)
تهدف هذه الدراسة إلى بيان الأسس الفقهية العامة التي تُشكِّل المنطَلَق للفهم والإفتاء في قضية فلسطين والمسجد الأقصى المبارك، كما أنها تُعَبِّر عنْ مجموعة مِن الثوابت الشرعية التي لا يمكن تجاوزها مِن قِبَل أي شخص أو جهة تتصدر للفتوى في هذه القضية المحورية. إنّ كثرة الفتاوى والآراء الصادرة عن فئات مختلفة من العلماء والباحثين والدعاة التابعين لمذاهب متعددة، ومشارب متنوعة، فيما يخص القضية الفلسطينية مِن أحكام شرعية؛ يؤدي إلى خلط في المفاهيم، وتناقض في الفتاوى، واختلاف في الأحكام، منشؤه عدم استناد أصحاب هذه الآراء والفتاوى إلى أسس فقهية صلبة، وثوابت شرعية راسخة تحكم الاجتهاد، وتوجه الفكر، وتضبط الرأي عند الحديث عما يتعلق بهذه القضية من أحكام، الأمر الذي أحوج إلى إيجاد نموذج منضبط بالأصول مِن العلماء الراسخين العاملين المحيطين بكافة جوانب هذه القضية لدراسة فكره الفقهي فيها، بحيث تعتبر آراؤه منطلقًا يمكن أن يَستند إليه كل متصدر للفتوى في هذه القضية. وعليه فسيقوم الباحثون باستقراء ما وصلت إليه أيديهم مما خطه القرضاوي بيده، أو قاله بلسانه، لتجتمع عندهم مادة هذا البحث العلمية، ثم يعمدون إلى تحليلها وتفكيك أجزائها من خلال المنهج التحليلي، ولن تكتمل الصورة إلّا بإعادة تركيب عناصرها، وتجميع مفرداتها؛ ليَصِلوا من خلال ذلك كله إلى رسم صورة متكاملة الأجزاء، واضحة المعالم حول الأسس والثوابت التي يجب أن تكون حاضرة عند كل من يتصدر للفتوى في هذه القضية. وعليه فقد توصلت هذه الدراسة إلى أنّه لا بُدّ أولًا مِن بناء الفكر وتأصيل الوعي بهذه القضية، كما أن فلسطين أرض عربية إسلامية لا حق لليهود فيها أبدًا، وأن الاحتلال الصهيوني لهذه الأرض هو سبب الصراع وأصل المعركة، كما أكدت هذه الدراسة على إسلامية القضية الفلسطينية، فطابعها ديني، وهي جزء من العقيدة، ومتعلقة بجميع المسلمين، ويترتب عليها أحكامًا شرعية، كوجوب الجهاد، وحرمة الهجرة منها، وكذلك تحريم زيارتها في ظل الاحتلال، وأنه يحرم السلام مع إسرائيل أو تطبيع العلاقات معها، وأن التنازل عن القدس أو عن أي ذرة تراب منها، أو حتى قبول التعويض يعتبر خيانة لله ولرسوله وللمؤمنين، والواجب مقاطعة الاحتلال بكافة أشكال المقاطعة وأنواعها، ويحرم التعاون مع الأعداء بأي شكل مِن الأشكال، وأخيرًا فإن الحل لهذه القضية لا يكون إلّا بالرجوع إلى الإسلام وتعاليمه، والتزام أحكامه وما يترتب عليها من واجبات تجاه هذه القضية. ======== This study seeks to articulate the overarching juristic principles that underpin the understanding and issuance of legal opinions (fatwas) regarding the Palestinian question and the status of al-Aqsa Mosque. It also identifies a set of non-negotiable Shariah constants that must be observed by any authority addressing this highly sensitive matter. The proliferation of fatwas and opinions issued by scholars, researchers, and preachers from various schools and intellectual orientations has often resulted in conceptual confusion, conflicting verdicts, and divergent legal judgments. Such discrepancies largely stem from the absence of a solid juristic foundation and well-established Shariah parameters to regulate ijtihad, discipline legal reasoning, and guide scholarly discourse on this issue. To address this gap, the study turns to the juristic thought of Shaykh Yusuf al-Qaradawi, a scholar widely recognized for his profound engagement with the Palestinian cause. By collecting his written works and recorded statements, the researchers employ an analytical methodology to deconstruct, examine, and then reconstruct his arguments in order to present a coherent framework. This framework provides a structured reference for scholars and jurists undertaking the task of issuing fatwas on the matter. The findings highlight several key conclusions: foremost, that sound awareness and principled intellectual grounding are prerequisites for any engagement with the Palestinian issue. The study affirms that Palestine is an Arab and Islamic land to which Jews hold no legitimate claim, and that Zionist occupation remains the root cause of the conflict. It emphasizes the religious character of the Palestinian cause as an integral part of Islamic faith, carrying significant legal implications—such as the obligation of jihad, the prohibition of migration from its lands, the impermissibility of visiting it under occupation, and the unlawfulness of peace treaties or normalization with Israel. Any concession of Jerusalem, or of even a fraction of its land, whether through negotiation or compensation, is considered an act of betrayal against Allah, His Messenger, and the believers. The study further underlines the duty to boycott the occupier in all forms and the prohibition of collaboration with adversaries. Ultimately, it concludes that a just resolution to this issue can only be achieved through adherence to Islam, its principles, and the obligations it enjoins concerning Palestine.